The cognitive outcome in athletics among physical education teachers - Ismaiel, Ismaiel Ghasab; Oudat, Mo'een Ahmad; Thiyabat, Mohammad Khalaf; Alshdokhi, Khaled Abdullah (Institute of Advanced Engineering and Science, 2024)
The study aimed to identify the cognitive outcome in athletics for physical education teachers. The descriptive survey method was used and a cognitive test was applied as a measurement tool for data collection, which included 45 items for the fields of study: running, jumping, and throwing, and the study sample consisted of 198 teachers from Irbid First Directorate of Education in the first academic semester 2022/2023. The results showed that the level of the cognitive outcome in athletics for physical education teachers was